Carbon dioxide fixation and utilization by conversion to biomass using microalgal photobioreactor - Linh, Le Thi Hong (Animo Repository, 2006)
Global warming is a major environmental problem that needs to be addressed. One of the major industrial exhausts that caused global warming is carbon dioxide. It is necessary to find an efficient and economical way to capture it and recycle it back before it reached the upper atmosphere. One promising method is to convert the CO2 into algal biomass by photosynthesis in a controlled microalgal photobioreactor. In this study, the kinetic parameters were determined by running batch flask photobioreactor. In addition, the continuous flask photobioreactor was operated under varying of ratio CO2, gas flow rate, light intensity and hydraulic retention time (HRT) to investigate the characteristic of photosynthetic microalgae inside the photobioreactor. Microalga, Chorella Sorokiniana 211/8k strain, was used to evaluate the reduction of CO2 by converting it to algal biomass. Inlet and outlet gas compositions were measured by using Hempl apparatus. The result of nonlinear regression showed that Haldane with endogenous metabolism (Endo-Haldane model) was the suitable model to describe the data of the kinetic test. By using Taguchi method the optimum operating conditions were obtained with 7.5% CO2, 0.05 vvm, 400 lux in light intensity and 2 days HRT. Under optimum operating conditions, the amount of CO2 reduced was 2.5g CO2/L/day and the efficiency of CO2 removal was nearly 35% based on mass of carbon dioxide removed from the gas phase. This systems efficiency could be further improved by using optimization techniques and the results could be applied in absorbing CO2 exhausted from large scale power generating plants using fossil fuels.